Can Rational Combination of Ultra-high Dose Rate FLASH Radiotherapy with Immunotherapy Provide a Novel Approach to Cancer Treatment?. Issue 11 (November 2021) - Zhang, Y.; Ding, Z.; Perentesis, J.P.; Khuntia, D.; Pfister, S.X.; Sharma, R.A.
Abstract: FLASH radiotherapy (FLASH-RT) delivers radiation treatment at an ultra-high dose rate that is several orders of magnitude higher than current clinical practice. In multiple preclinical studies, FLASH-RT has shown consistent normal tissue sparing effects while preserving equivalent antitumour activity in comparison with conventional dose rate radiation treatment. This is known as the 'FLASH effect'. Given the recent research interest in combining hypofractionated radiotherapy with immunotherapy to try to improve clinical outcomes, there is an intriguing clinical question as to whether FLASH irradiation may be a rational partner to combine with immune modulating drugs? To better predict the synergistic effect of both modalities, here we review the biological mechanisms of how FLASH differentially impacts the immune landscape, including circulating immune cells, tumour microenvironment and the inflammatory response. In order to make recommendations for future research, we summarise all published studies that investigated the immune modulatory effects of FLASH-RT and further explore the scientific reasons for combining FLASH with immunotherapy for potential clinical applications.